The sphinx of the Charles : a year at Harvard with Harry Parker - Ayer, Toby (Lyons Press, 2016)
Harry Parker was probably the most important figure in American rowing of the past century. His heavyweight crews at Harvard topped the leagues more consistently than any other team (they won the Eastern Sprints regatta, against most of the top college crews, more than three times as often as their nearest rival). From the time they miraculously won the 1963 Harvard-Yale Race at the end of his first year at the helm, his varsity didn't lose a race for six years, and they didn't lose to Yale until the Reagan administration. He was the first US National Team coach, and oversaw five Olympic teams.
Keywords: Parker, Harold Lambert, -- 1935-2013.; Ayer, Toby.; Harvard University -- Rowing -- History.; Ayer, Toby; Parker, Harold Lambert, -- 1935-2013; Harvard University; Rowing coaches -- Massachusetts -- Biography.; Aviron -- Entraîneurs -- Massachusetts -- Biographies.; SPORTS & RECREATION -- Water Sports.; Rowing; Rowing coaches; Massachusetts; Biographies; History